Dosimetric results in treatments of neuroblastoma and neuroendocrine tumors with 131I‐metaiodobenzylguanidine with implications for the activity to administer. Issue 7 (10th June 2015) - Mínguez, Pablo; Flux, Glenn; Genollá, José; Guayambuco, Sonía; Delgado, Alejandro; Fombellida, José Cruz; Sjögreen Gleisner, Katarina
Abstract : Purpose: The aim was to investigate whole‐body and red marrow absorbed doses in treatments of neuroblastoma (NB) and adult neuroendocrine tumors (NETs) with 131 I‐metaiodobenzylguanidine and to propose a simple method for determining the activity to administer when dosimetric data for the individual patient are not available. Methods: Nine NB patients and six NET patients were included, giving in total 19 treatments as four patients were treated twice. Whole‐body absorbed doses were determined from dose‐rate measurements and planar gamma‐camera imaging. For six NB and five NET treatments, red marrow absorbed doses were also determined using the blood‐based method. Results: Dosimetric data from repeated administrations in the same patient were consistent. In groups of NB and NET patients, similar whole‐body residence times were obtained, implying that whole‐body absorbed dose per unit of administered activity could be reasonably well described as a power function of the patient mass. For NB, this functional form was found to be consistent with dosimetric data from previously published studies. The whole‐body to red marrow absorbed dose ratio was similar among patients, with values of 1.4 ± 0.6–1.7 ± 0.7 (1 standard deviation) in NB treatments and between 1.5 ± 0.6 and 1.7 ± 0.7 (1 standard deviation) in NET treatments. Conclusions: The consistency of dosimetric results between administrations for the same patient supports prescription of the activity based on dosimetry performed in pretreatment studies, or during the first administration in a fractionated schedule. The expressions obtained for whole‐body absorbed doses per unit of administered activity as a function of patient mass for NB and NET treatments are believed to be a useful tool to estimate the activity to administer at the stage when the individual patient biokinetics has not yet been measured.